Pengaruh Kompensasi, Disiplin Kerja, Lingkungan Kerja, Terhadap Produktivitas Karyawan di PT. Sarana Bangun Pusaka - Perdana, Reza Kresna; Waluyo, Dwi Eko (Jurnal EMT KITA, 2024)
The purpose of this study was to analyse the effect of compensation, work discipline, work environment, and leadership style on employee productivity at PT. Sarana Bangun Busaka. This research method is quantitative. In this study, the population used was the productivity of employees of PT. Sarana Bangun Pusaka. This research uses non-probability sampling. The sample was taken by purposive method. This study used a sample of 70 respondents. The data needed in this study is Primary Data. The data analysis technique is with the help of SPSS software. The results of this study are Employee productivity gets a significant effect partially from compensation. Employee productivity has a significant effect partially on work discipline. Employee productivity gets a significant effect partially from the work environment. Employee productivity does not get a significant effect partially from leadership style. Simultaneously the value of employee productivity is influenced by compensation, work discipline, work environment, and leadership style.